Why Triple Helix governance is useful to dual apprenticeship systems. Issue 6 (December 2019) - Coletti, Michele
Apprenticeship is a contractual form of work-based learning that has existed for centuries, but despite its historical impact on innovation and competitiveness, it has been perceived as a system for the shop floor or low-skill jobs. The dual apprenticeship system combines school study with training on the job. Well developed in several European countries it can lead to highly qualified jobs, so attracting the interest of universities and other higher education institutions. Academic, business and government stakeholders working together enact a Triple Helix (TH) framework. This article analyses how the TH is suitable for the governance of apprenticeship systems and discusses the implications of the model.